Gaya Kepemimpinan Situasional pada Motivasi Kerja Karyawan Generasi X, Y dan Z: Studi pada PT. Blue Ocean Heart Area B Malang - Dewantari Puteri Yuananda; Eko Agus Alfianto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
In today's digital era and generational diversity, leadership plays a crucial role in creating a productive and harmonious work environment. This study aims to analyze the application of situational leadership style at PT. Blue Ocean Heart Area B Malang on employee work motivation from generations X, Y, and Z. The method used involves a qualitative descriptive approach with data collection through interviews and observations. The results of the study indicate that a flexible and responsive situational leadership style to differences in generational characteristics can improve employee motivation and performance. Generation X values ​​stability and autonomy, Generation Y seeks recognition and development, while Generation Z is more motivated by innovation and inclusiveness. These findings emphasize the importance of leaders' adaptive abilities in managing multigenerational teams to achieve organizational goals effectively.